ANALISIS KARAKTERISTIK INDIVIDU, DIFERENSIASI PRODUK DAN HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN - Nurochman, Gina (2012)
Cross Mobile is a mobile phone with Europe standard technology, with the adjustment of the product to the different individual characteristics, diverse product differentiation, and prices are relatively low, but can not enter the popular mobile phones ranking consumer choice in Bandung, suspected consumer buying decision process on the Cross mobile phone less supports. Therefore it is necessary to measure, analyze the individual characteristics, product differentiation and price how much influence on Cross mobile phone buying decision process. The study was conducted to one hundred respondents buyers at the counter mobile phones Cross Bandung Electronic Center, using the descriptive research method verification. Selected sampling systematic random sampling technique. Data was collected through questionnaires, interviews and literature. To measure the influence of individual characteristics, product differentiation and price of the buying decision process, the technique used path analysis. The results showed that the process of buying decisions are influenced positively by each variables of individual characteristic, product differentiation and price. The companies should be conduct a variety of activities that provide knowledge about mobile phones Cross to stimulate motivation of consumers buying mobile phones Cross, as well as enhanced durability mobile phones Cross.